O problema da agência moral e política na filosofia de David Hume - Rodrigues, Cláudio Eduardo (2009)
This thesis analyzes and discusses the ideas of passion, reason, consenting, promise, and political obedience aiming to verify how they can found on a defense of morals and politics in David Hume s philosophy. From the rational view, Hobbes and Locke postulate that the institution and legitimating of political associations or of the State stem from people s liberty and interest in giving in to the other s power; from the making of agreements or deals related to the association or submission; and from the explicit promise of adhesion and obedience to the established government. From the human behavior observation and historical perspectives, Hume states that government s origin and legitimating don t rely on contracts and explicit promises of submission since political societies established through usurpation and conquering demand the same obedience and submission from people as other states do. Such a debate with contractualists reveals three problems in Hume s political philosophy: the passive and tacit character of political obedience to the usurped and conquered governs; the compatibility between the idea of spontaneity liberty or free action and the submission imposed by governments established through strength and violence; and the existence and operation of political and moral agents able to determine themselves in circumstances of social and political restraint. As a hypothesis of solution for such problems, one considers that morals and politics in Hume s philosophy can be established by taking human nature principles as the creative principle of all institutions and sciences. Therefore, one needs to verify the role reason and passions play in the determination of human behavior and constitution of the State; to distinguish the debate on the government origin from the debate on its legitimacy, so that to analyze the psychological principles which make people to accept being governed; to examine the general promise foundations, so that to note the motivations for the agreements fulfillment; and to investigate the obedience and legitimating principles in political societies.